2011
DOI: 10.4103/0972-3919.106707
|View full text |Cite
|
Sign up to set email alerts
|

Solid variant of papillary carcinoma thyroid in a child with no history of radiation exposure

Abstract: Solid variant is a rare and poorly characterized variant of papillary thyroid carcinoma (PTC) and comprises approximately 3% of PTCs. It is more common in children and has high propensity for extrathyroidal metastasis. It is seen in higher proportion in post-radiation PTCs and has been seen in more than one-third of post Chernobyl radiation induced PTCs in some studies. It usually presents with differential diagnosis of poorly differentiated carcinoma versus anaplastic versus medullary thyroid carcinoma versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…Damie et al 8 reported a case of a 12-year-old girl with left cervical lymphadenopathy, in which differential diagnoses of poorly differentiated carcinoma, medullary carcinoma, anaplastic carcinoma and metastatic carcinoma of the thyroid were considered; however, finally it was confirmed solid variant of PTC metastases to left cervical lymph nodes. In that case, fine needle aspiration cytology (FNAC) suggested a differential of Hurthle cell neoplasm or medullary carcinoma of the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Damie et al 8 reported a case of a 12-year-old girl with left cervical lymphadenopathy, in which differential diagnoses of poorly differentiated carcinoma, medullary carcinoma, anaplastic carcinoma and metastatic carcinoma of the thyroid were considered; however, finally it was confirmed solid variant of PTC metastases to left cervical lymph nodes. In that case, fine needle aspiration cytology (FNAC) suggested a differential of Hurthle cell neoplasm or medullary carcinoma of the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, it has been associated with childhood presentation, prior radiation exposure, and a less favorable prognosis than cPTC [17, 18]. However, a few authors have reported these tumors to have age and prognosis comparable to cPTC and no association with radiation exposure [4, 5, 18]. All our patients were also adults, with a mean age of 43.9 years.…”
Section: Discussionmentioning
confidence: 96%
“…Only 3 studies detailing cytological features of this rare variant have been published [7, 12, 18]; the rest are case reports or lack detailed description [4, 5, 19-22]. We retrospectively evaluated aspiration smears of 9 SVPTC cases we came across over a period of 3 years and compared their various cytomorphological features with those of NIFTP/FVPTC, cPTC, and PDTC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations